Transcription factor c-Myb is involved in the regulation of the epithelial-mesenchymal transition in the avian neural crest - Karafiat, V; Dvorakova, M; Krejci, E; Kralova, J; Pajer, P; Snajdr, P; Mandikova, S; Bartunek, P; Grim, M; Dvorak, M (Cellular and molecular life sciences, 2005)
Multipotential neural crest cells (NCCs) originate by an epithelial-mesenchymal transition (EMT) during vertebrate embryogenesis. We show for the first time that the key hematopoietic factor c-Myb is synthesized in early chick embryos including the neural tissue and participates in the regulation of the trunk NCCs. A reduction of endogenous c-Myb protein both in tissue explants in vitro and in embryos in ovo, prevented the formation of migratory NCCs. A moderate over-expression of c-myb in naive intermediate neural plates triggered the EMT and NCC migration probably through cooperation with BMP4 signaling because (i) BMP4 activated c-myb expression, (ii) elevated c-Myb caused accumulation of transcripts of the BMP4 target genes msx1 and slug, and (iii) the reduction of c-Myb prevented the BMP4-induced formation of NCCs. The data show that in chicken embryos, the c-myb gene is expressed prior to the onset of hematopoiesis and participates in the formation and migration of the trunk neural crest.
Keywords: Chick Embryo; Animals; Proto-Oncogene Proteins c-myb; epitel; Electroporation; transkripční faktory; Oligonucleotides, Antisense; protoonkogenní proteiny c-myb; kostní morfogenetické proteiny; Snail Family Transcription Factors; Transcription Factors; messenger RNA; Neural Crest; elektroporace; RNA, Messenger; Epithelium; Bone Morphogenetic Proteins; transkripční faktor MSX1; Mesoderm; mezoderm; kostní morfogenetický protein 4; MSX1 Transcription Factor; Antibody Specificity; rodina transkripčních faktorů Snail; specificita protilátek; antisense oligonukleotidy; zvířata; crista neuralis; Bone Morphogenetic Protein 4; kuřecí embryo